A Grammatical Error Analysis of the Students' Recount Text at the Eleventh Grade Students - Moh Choirul Huda; Piping Rahadianto (STKIP PGRI Trenggalek, 2021)
This study is aimed at analyzing the types of grammatical error, which is viewed from 4 categories such as Omission, Addition, Misselection, and Misordering, that the students do and which types of grammatical error which the students most frequently do in writing a recount text. The research design is a descriptive research with quantitative approach. The participants are the eleventh grade students of MA Sunan Giri Gondang in academic year 2020/2021 consisting of 20 students. To collect the data, the researcher uses writing test as the instrument then analyzes it based on these procedures, i.e. identifying, describing, and explaining. The findings show that there are 182 errors made by the students which are divided into some categories, i.e. Omission category was 47 (26%), Addition category was 20 (11%), Misselection category was 114 (63%), and Misordering was 1 (1%). Meanwhile, the most frequent error made by the students was Misselection category. Based on the findings, The teachers should pay more attention to the students’ grammar especially in language features of Recount text and motivate more the students to learn grammar by applying various kinds of teaching method. Furthermore, this research also can be as a reference for other researchers when conducting similar research with different participant